Tabayyun in the Digital Age: Islamic Ethical Verification Against Misinformation and Online Deception - Rosninawati Hussin; Suria Hanni A. Rahman; Sofia Hayati Yusoff; Fauziah Hassan (Jogjakarta Communication Conference (JCC), 2026)
The expansion of digital media has intensified the spread of misinformation, speculative narratives, and online deception. In this environment, the absence of verification often leads to reputational harm, financial scams, and the rapid spread of misleading information. This paper explores the Islamic principle of tabayyun—verification before accepting or disseminating information, as an ethical framework for responsible digital communication. Drawing upon Qur’anic guidance in Surah al-Hujurat (49:6), the study situates tabayyun within Islamic communication ethics emphasizing trust (amanah), justice (‘adl), and the protection of human dignity. The discussion examines how digital virality, clickbait culture, and online scams exploit the lack of user verification. While cases such as viral social media controversies illustrate the phenomenon, the paper extends the discussion to broader issues of digital misinformation and deception. It argues that tabayyun offers both a moral and practical framework for navigating contemporary information ecosystems by promoting critical verification, ethical restraint, and responsible sharing practices. Ultimately, the study highlights how Islamic ethical principles can contribute to global conversations on digital media responsibility, misinformation management, and the preservation of social trust in networked societies.